Keluarga yang Berpusat pada Injil Eksposisi Surat Efesus 6:1-4 - Gian Gideon Akin (Voice, 2022)
The aim of this article is to gain an understanding of the exposition of Ephesians 6:1-4 and its application to the roles and responsibilities of parents and children in a Christian family. In this article, the author describes the way of life of believers, especially how the relationship between parents and children in Christ. The method used in this writing is a qualitative research method with a literature study and hermeneutic approach. The data comes from Christian articles, Bible commentary books, and other sources. This research results in an interpretation of the epistlemEphesians 6:1-4 as well as the application that can be applied within the scope of the Christian family.